2020
DOI: 10.1002/nop2.724
|View full text |Cite|
|
Sign up to set email alerts
|

Internet‐based interventions for postpartum depression: A systematic review and meta‐analysis

Abstract: Aim To determine the efficacy of Internet‐based interventions in decreasing the prevalence of postpartum depression in perinatal women. Design This review was conducted according to the standards outlined in the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Methods We performed a systematic meta‐analysis of randomized controlled trials on the efficacy of Internet‐based interventions for postpartum depression. Studies (2008–2018) were identified through a search conducted on PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 57 publications
1
21
0
1
Order By: Relevance
“…The results revealed that the participants in the intervention group, who participated in CBT self-help programs with weekly minimal guidance, signi cantly improved their depression symptoms with medium to large effect size of -0.60 at post-intervention compared with those in the control group. This result approximates the effect size of 0.64 [57] and effect size of 0.63 [58] reported in previous metaanalyses. In a recent systematic review and meta-analysis [59] from 2021, it was also found that guided internet-based CBT was associated with more effectiveness in reducing depressive symptoms than control conditions.…”
Section: E Cacy Of Computer-and/or Internet-based Cbt Self-help Treat...supporting
confidence: 90%
“…The results revealed that the participants in the intervention group, who participated in CBT self-help programs with weekly minimal guidance, signi cantly improved their depression symptoms with medium to large effect size of -0.60 at post-intervention compared with those in the control group. This result approximates the effect size of 0.64 [57] and effect size of 0.63 [58] reported in previous metaanalyses. In a recent systematic review and meta-analysis [59] from 2021, it was also found that guided internet-based CBT was associated with more effectiveness in reducing depressive symptoms than control conditions.…”
Section: E Cacy Of Computer-and/or Internet-based Cbt Self-help Treat...supporting
confidence: 90%
“…Moreover, a large study capturing a wider demographic of women including those with reduced access to the internet and low technology literacy is lacking. Lastly, little is known about the rates of dropout from internet-based interventions for perinatal depression and anxiety symptoms, with reported rates ranging widely from 4.5–86% [ 40 , 41 ], and lack of information on factors determining dropouts and non-responses [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to evaluate the effects of nonpharmacologic interventions on postpartum women experiencing PPD. In the existing literature, psychosocial intervention [11][12][13][14][15] and physical intervention [16][17][18][19] have been identified to be associated with a reduction in the likelihood of continued PPD, which mainly used traditional face-to-face method.…”
Section: Introductionmentioning
confidence: 99%
“…E-health technology was the innovative approach of intervention delivery that uses online technology [26], with the distinguished advantages of improved flexibility, accessibility, and reduced financial and time cost [27]. The random-effects model of a recent meta-analysis indicated that the internet-based interventions have proven to be effective in the reduction of PPD symptoms (d = 0.642, N = 7) [13]. However, all the seven randomized controlled trials (RCTs) for PPD based on internet had been conducted in developed countries, such as UK, USA, Canada, Australia, and Sweden [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation